Bibliotherapy as an Intervention among university student with Black Mail - Abdul Mahdi Mohamed Ali Gemayel, Zahraa (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the effect of bibliotherapy as an intervention for blackmail female students in Al Mustansiriyah University. For 344 female students ages 19-22, they fulfilled blackmail questions that consisted of 19 items. 32 subjects who received higher scores on the questionnaire were selected through a randomized sample of art college. Interventions based on the bibliotherapy approach were done on 32 participants in 14 one-hour sessions. All participants fulfilled the questionnaire another time. Data were collected by Black Mail and analyzed by SPSS software through a t-test for two matched samples. the results revealed significant differences (p > 0.05) in postinterventional phase for approval to mean scores Pre-intervention, these results provide some evidence that the bibliotherapy has effectiveness in preventing the participants from being victims to blackmailers.